Comparison of ease of intubation in patients using C-MAC D-Blade between simulated cormack lehane 1 and 2 videolaryngoscopic view : a randomised controlled trial - Semanat, Ahmad Shamil (2020)
Background: Difficult intubation could result in both morbidity and mortality. Current surging popularity with videolaryngoscope such as C-MAC D-Blade can reduce the risk of complications associated with difficult intubation. Despite showing good glottis view, the unique laryngoscope shape could pose a problem during tracheal intubation. Having a lesser appearance of the glottis may hypothetically ease the endotracheal tube delivery. This study compares the ease of intubation in patients using C-MAC D-Blade between simulated Cormack Lehane 1 and 2 videolaryngoscopic view among adult patient undergoing elective surgery. Methods: 94 adults with no features of difficult intubation undergoing elective surgical procedures in Hospital Universiti Sains Malaysia Kelantan were recruited and randomly assigned to two groups either A for Cormack Lehane 1 (n=46) or B for Cormack Lehane 2 (n=48) videolaryngoscopic view. The outcome measured include duration of intubations, number of intubation attempts, and easiness of intubations. Results: Duration of intubation was less (7.7 ± 1.93s) in Group B than in Group A (9.2 ± 2.49s) with a mean difference of 1.4s (95% CI=0.53, 2.35, p=0.002). There is no significant difference between the two groups in terms of the number of intubation attempts (p=0.322) and easiness of intubation (p=0.78). Conclusion: Cormack-Lehane 2 videolaryngoscopic view significantly reduce time to intubation compared to Cormack-Lehane 1 videolaryngoscopic view when using C-MAC D-Blade.